A Vindication of Simondon's Political Anthropology. Issue 1 (2nd January 2018) - Bardin, Andrea; Rodriguez, Pablo
Abstract: This article questions Balibar's claim that Simondon's concept of the transindividual does not fulfil all the requirements (the 'three orders of consideration') for a materialist 'philosophical anthropology'. In fact, we demonstrate that Simondon's philosophy of individuation, and notably his concept of the transindividual, can be, as it were, included in a genealogy of aleatory materialism. Simondon's philosophy of individuation is indeed a philosophy of the transindividual insofar as it involves the constant revision of the different historical forms taken by social relations in the coevolution of human beings and their techno-social and natural milieu. Simondon's way of conceiving anthropogenesis as an open and 'metastable' field in which individuals and processes relate to each other maintaining their own knowledge in motion, marks, in our view, a materialist style of thinking. Against this background we analyse Simondon's overcoming of the dichotomy between the individual and society through a 'double rejection', we sketch his theory of a 'double source' for social relations, and we explain in what sense, from his perspective, the transindividual 'can be said in many ways'.